Pengaruh Kualitas Produk, Harga, Dan Promosi Terhadap Keputusan Pembelian Melalui Kualitas Pelayanan Sebagai Variabel Intervening Di Rumah Makan “Andina” Muara Teweh Kabupaten Barito Utara Provinsi Kalimantan Tengah - Murnilawati Murnilawati; Hairudinor Hairudinor; M Nor Rasyidi¬ (JURNAL BISNIS DAN PEMBANGUNAN, 2019)
Restaurant Andina is one of the restaurants in Muara Teweh on monthly sales turnover and increase and decrease of sales in every month always decrease and increase. This study aims to determine whether there is influence Influence Products, Prices and Promotion Against Decision Purchase Through Quality Service employees either partially or simultaneously.The method used in this study is quantitative research that is a research model that requires the existence of the calculation of the numbers, while the approach used is the survey approach that is the research that takes the sample of 117 of the population and use the questionnaire as a basic data collection tool.The results of this study indicate that, the variable quality of service does not significantly influence the Quality of Service, the price significantly influence the Quality of Service, the promotion does not significantly affect the Quality of Service, product quality does not significantly affect the Quality of Service, Purchase Decision, service quality variable has no significant effect on Purchasing Decision, Price variable has significant effect to service quality and service quality has significant effect on purchasing decision. Promotion variable has significant effect to service quality and service quality has significant effect to purchasing decision. Keywords: Quality, Product, Price, Promotion, Purchase Decision